Methods and Applications of Structure Based Pharmacophores in Drug Discovery - Pirhadi, Somayeh; Shiri, Fereshteh; Ghasemi, Jahan B. (Current Topics in Medicinal Chemistry, 2013)
A pharmacophore model does not describe a real molecule or a real association of functional groups but illustrates a molecular recognition of a biological target shared by a group of compounds. Pharmacophores also represent the spatial arrangement of essential interactions in a receptor-binding pocket. Structure based pharmacophores (SBPs) can work both with a free (apo) structure or a macromolecule-ligand complex (holo) structure. The SBP methods that derive pharmacophore from protein-ligand complexes use the potential interactions observed between ligand and protein, whereas, the SBP method that aims to derive pharmacophore from ligand free protein, uses only protein active site information. Therefore SBPs do not encounter to challenging problems such as ligand flexibility, molecular alignment as well as proper selection of training set compounds in ligand based pharmacophore modeling. The current review deals with ‘Hot Spot’ analysis of binding site to feature generation, several approaches to feature reduction, and considers shape and excluded volumes to SBP model building. This review continues to represent several applications of SBPs in virtual screening especially in parallel screening approach and multi-target drug design. Also it reports the applications of SBPs in QSAR. This review emphasizes that SBPs are valuable tools for hit to lead optimization, virtual screening, scaffold hopping, and multi-target drug design.
Keywords: Parallel screening